Cultural participation in the main Colombian cities, 2008-2015 (2019)
This paper aims to explain the evolution of the cultural participation in Colombia between 2018 and 2015, and to empirically analyse the factors associated to the decision of participating in cultural activities in the five main cities during this period. In Bogota, Cali, Medellin, Barranquilla and Cartagena, half of the urban population resides. The effects of a set of individual variables, household and context are evaluated, exploring alongside the traditional determinants, a set of new variables such as the kind of education that children receive, the poverty situation and others concerning the habitat, the social capital and macroeconomic ones. Microdata from households from the Quality of Life Survey - from programmes of citizen monitoring- are used, with which a binomial model is estimated. The results highlight the importance of including the context variables so as to widen the knowledge of the individual decisions of participation. © 2019 Alexandru Ioan Cuza University of Iasi.